Sharia Marketing Strategy Education in Increasing Customer Trust in Pawn and Gold Installment Products at Bank Syariah Indonesia KCP Pandeglang - Rohmatun Nadia Maulida (Penerbit Hellow Pustaka, 2024)
Marketing strategy education plays a very important role in the success of the company, which must be reviewed and developed in accordance with the development of the market and the market environment. The purpose of this study is to determine sharia marketing strategies in increasing customer trust and find out the factors that hinder the growth of customer trust in pawn financing products and gold installments at Bank Syariah Indonesia KCP Pandeglang. This research is a type of field research that involves interview, observation and documentation data collection techniques. Data analysis using an inductive approach, the subject of this study is Bank Syariah Indonesia KCP Pandeglang. The results of this study show that the marketing strategies used by Bank Syariah Indonesia KCP Pandeglang including shiddiq, amanah, tabligh, fathonah, syaja'ah are very good in building customer trust. However, behind all that, the facts of this study show that Bank Syariah Indonesia KCP Pandeglang still has many obstacles, especially in marketing, such as the lack of public understanding of the Islamic banking system and public ownership interest in gold bars. In relation to marketing pawn financing products and gold installments, Bank Syariah Indonesia KCP Pandeglang implements Islamic principles, such as Godly, Ethical, Realistic and Humanist. This is evident from the implementation of the 4S principles (Smile, Greetings, Polite, Courteous as a form of ethics and humanism. As well as prioritizing open information as a form of realistic unity.